Firm Productivity and Carbon Leakage: A Study of Swedish Manufacturing Firms - Shon Ferguson; Mark Sanctuary (Research Institute of Industrial Economics (IFN), 2014)
This paper examines the intensive and extensive margins of carbon leakage. The analysis uses an increase in the Swedish electricity price to identify the impact on imports at the firm and product level. Our model of heterogenous firms predicts that higher domestic electricity prices lead firms to substitute towards imports of electricity-intense products.
Keywords: D21; F18; 330; Firm heterogeneity; Carbon leakage; Energy; Importing